Return as the Idea of Creating Surrealist Paintings - rahmadhani, syifa; Miswar, Miswar; Muler, Yunis (V-art: Journal of Fine Art, 2023)
Going home is defined as returning to the origin. The word "home" meant is reviewed based on the essence of taste, namely returning to feelings or situations that have been experienced with the aim of evaluating or reinterpreting phenomena and experiences that have occurred, as well as education and learning for the future. This leads to more complex emotions, namely comfort, calm, emotion, sadness and relieved. Going home is also a method of controlling emotions, namely emotional focused coping in dealing with the diverse dynamics of life. The feeling of going home becomes an idea in creating works of art. The presence of this work becomes a documentation of the journey and feelings of returning home and triggers a deep awareness of the importance of every process and experience that is passed. The form of works of art embodied in figurative form by distorting and transforming the canvas using the placard technique. The creation method carried out at the preparatory stage is by observing objects which include human anatomical structures, gestures to facial expressions. In addition, contemplation was also carried out to recall the feeling of returning home that had been experienced. Furthermore, at the design stage includes visual strategies, sketches and selecting sketches, then at the embodiment stage, the preparation of tools and materials is carried out and the transfer of sketches to canvas media, the painting process, finishing up to the stage of presenting the work in the exhibition room. The embodiment of the concept of going home produced five works of art with the titles "Rest", "Just a Moment", "Sad", "Hug" and "Medicine".